The Scenic Performance as Subversive Negativity: radical alterity and trava sudaca performance in the voice of Susy Shock - Martínez, Ariel; Mora, Ana Sabrina (Revista Brasileira de Estudos da Presença, 2020)
Considering the scenic performances of the artist Susy Shock, and in particular the stage presentation she makes of a so called monstrosity that maintains a series of elements that make up a scenic performance where the monstrosity can break into the field of intersection and conjugation, we offer some epistemological thoughts about the limits of identity representations versus stage presentations. Her poetic performances include songs of musical genres of Argentine folklore (vidalas, coplas, tangos), through the appropriation of a traditional cultural product in the voice of a transgender person. This produces the visibility of a radical alterity in the simultaneous presentation of elements that can only be recovered from the intersectionality that is released in the ground of presentation, where all the elements break into overlap at the same time and in the same place.